TOURISM DEMAND MODELING: PRICE AND INCOME ELASTICITY - Kusumah, A.H.G (Journal of Indonesian Tourism, Hospitality and Recreation)
This paper provides a tourism demand model that estimates the price elasticity of demand and income elasticity of demand in Australia, European Union (EU), and USA. The results show that Australia and EU tourists markets are price elastic, while USA market is slightly price inelastic. It indicates that both Australia and EU tourists markets are sensitive to the tourism price while USA market is not. The study also found that the income elasticity of demand from the three markets is relatively income inelastic. In other words, tourism demand in the three markets is unresponsive to a change in income.Keywords: Tourism Demand, Price ElasticityThis paper provides a tourism demand model that estimates the price elasticity of demand and income elasticity of demand in Australia, European Union (EU), and USA. The results show that Australia and EU tourists markets are price elastic, while USA market is slightly price inelastic. It indicates that both Australia and EU tourists markets are sensitive to the tourism price while USA market is not. The study also found that the income elasticity of demand from the three markets is relatively income inelastic. In other words, tourism demand in the three markets is unresponsive to a change in income.